2023
DOI: 10.3390/agrochemicals2030023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Results of Pesticide Residue Analysis in Food Sampled between 2017 and 2021

Abstract: As mandated by the EU and the national risk management duties, pesticide residues were determined by four specialized laboratories in 9924 samples taken from 119 crops of economic importance in Hungary and imported foodstuffs during 2017–2021. The screening method applied covered 622 pesticide residues as defined for enforcement purposes. The limit of detection ranged between 0.002 and 0.008 mg/kg. The 1.0% violation rate concerning all commodities was lower than in the European Union. No residue was detectabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Their potential assets have been outlined in the literature recently [44,45]. In particular, in the context of environmental toxicity, biodegradable limonoids are less harmful than older synthetic pesticides, which persist as pesticide residues in crops in fields or are washed into surface water and end up contaminating drinking water or food plants and fruits, all of which can be detected in pesticide residue analyses [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Their potential assets have been outlined in the literature recently [44,45]. In particular, in the context of environmental toxicity, biodegradable limonoids are less harmful than older synthetic pesticides, which persist as pesticide residues in crops in fields or are washed into surface water and end up contaminating drinking water or food plants and fruits, all of which can be detected in pesticide residue analyses [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Pesticide residue monitoring results revealed that a substantial proportion of samples contain multiple residues. In Hungary, 36-50% of samples contained multiple residues ranging from 2 to 23 during 2017-2021 [13]. The frequency of multiple residues was in the same range in European countries.…”
Section: Introductionmentioning
confidence: 89%
“…Pesticide residues in food and environmental samples are monitored in many countries to various extents [13]. One of the main objectives of the monitoring program is to provide data on the dietary exposure assessment of consumers.…”
Section: Introductionmentioning
confidence: 99%
“…However, this analysis has a systemic approach and its object of study is agri-food systems and specifically an approach is made to the chemical substances used for agricultural and livestock production (agrochemicals, antibiotics and growth regulators). Currently, residues are being detected in practically all food chains of various products, such as bread, cereals, vegetable oil, fruit juices, fruits, beer, wine, honey, eggs and others (Khazaal et al, 2022;Rivas-Garcia et al, 2022;Ambrus et al, 2023). These types of substances are used massively in practically all agri-food production processes.…”
Section: Food and Healthmentioning
confidence: 99%